Vitamin D deficiency is associated with ethnicity and knee pain in a multi‐ethnic South‐East Asian nation: Results from Malaysian Elders Longitudinal Research (MELoR). (3rd April 2018) - Mat, Sumaiyah; Jaafar, Mohamad Hasif; Sockalingam, Sargunan; Raja, Jasmin; Kamaruzzaman, Shahrul Bahyah; Chin, Ai‐Vyrn; Abbas, Azlina Amir; Chan, Chee Ken; Hairi, Noran Naqiah; Othman, Sajaratulnisah; Cumming, Robert; Tan, Maw Pin
Abstract: Aim: To determine the association between vitamin D and knee pain among participants of the Malaysian Elders Longitudinal Research (MELoR) study. Method: This was a cross‐sectional study from the MELoR study consisting of a representative group of 1011 community‐dwelling older persons (57% female), mean age 86.5 (54–94) years; 313 were Malays, 367 Chinese and 330 Indians. Participants were asked if they had knee pain. Levels of serum 25‐hydroxy cholecalciferol (25‐[OH]D), an indicator of vitamin D status, were measured using routine laboratory techniques. Results: In unadjusted analysis, presence of knee pain was significantly associated with vitamin D deficiency (odds ratio [OR] 1.42; 95% confidence interval (CI) 1.08–1.85, P 0.011). Vitamin D levels were significantly associated with ethnicity differences where Malays (OR 7.08; 95% CI 4.94–10.15) and Indians (OR 6.10; 95% CI 4.28–9.71) have lower levels of vitamin D compared to Chinese. Subsequent multivariate analysis revealed that the association between vitamin D deficiency and knee pain was confounded by ethnic differences. Conclusion: A previous study suggested that vitamin D deficiency was associated with knee pain. This relationship was reproduced in our study, but we further established that the association was explained by ethnic variations. As vitamin D status is dependent on skin tone, diet and sunlight exposure, which are all effected by ethnicity, future studies are now required to determine whether a true relationship exists between vitamin D and knee pain.